Evaluation of thermic efects of single-walled carbon nanotubes functionalized with folic acid (Revista de Investigaciones Universidad del Quindío, 2013)
This project studied the functionalization of carbon nanotubes single wall (NTC) with folic acid (FA) and it was also measured the rise in temperature of aqueous solutions of NTC-AF irradiated with commercial  incandescent bulb, which mainly emit infrared radiation. The functionalization process was inspired from a synthesis method used for the amination of the lipase B from Candida Antarctica, EDAC is used as activating agent of the carboxyl groups present on the NTC surface. The materials were characterized mainly by IRATR and DLS.It was observed an increase in temperature of the functionalized na notubes when irradiated with a 60 W light bulb for an hour. The importance of achieving an increased temperature of this biomaterial under irradiation is its application in thermal therapeutic treatment. It’s an alternative method to eliminate cancer cells or those infected with parasites such as Leishmania, in which the diseased cells may “burn” by localized thermal effect.
Keywords: Carbon Nanotubes; Folic Acid; Functionalization; Irradiation I.R; thermal effect